Participation of TLR2 and TLR4 in Cytokines Production by Patients with Symptomatic and Asymptomatic Chronic Chagas Disease - Mendes da Silva, L. D. [UNESP]; Gatto, M. [UNESP]; Miziara de Abreu Teodoro, M. [UNESP]; de Assis Golim, M. [UNESP]; Pelisson Nunes da Costa, A. [UNESP]; Capel Tavares Carvalho, F. [UNESP]; Ramos Rodrigues, D. [UNESP]; Cï¿½mara Marques Pereira, P. [UNESP]; Victoriano de Campos Soares, M. [UNESP]; Calvi, S. A. [UNESP] (Wiley, 2017)
Chagas disease (CD), caused by the protozoan Trypanosoma cruzi, is a serious public health issue. Its evolution involves an acute stage, characterized by no specific symptoms, and the chronic stage during most individuals are asymptomatic, but about 30–40% of them become symptomatic presenting the cardiac or digestive disease. Host immune response mechanisms involved in symptomatic or asymptomatic chronic disease are not fully understood. The pro-inflammatory cytokines are crucial in host resistance. However, a fine control of this inflammatory process, by action of anti-inflammatory cytokines, is necessary to avoid tissue injury. This control was found to be responsible for no clinical manifestations in asymptomatic individuals. Toll-like receptors (TLRs) are extremely important in defining the cytokine profile released in response to a micro-organism. We found that patients with the cardiac form predominantly released the pro-inflammatory cytokines: IFN-γ, TNF-α and IL-17 with the involvement of both, TLR2 and TLR4. In contrast, patients with asymptomatic disease release predominantly the anti-inflammatory cytokines IL-10 and TGF-β, but also with TLR2 and TLR4 participation. The mechanisms by which stimulation of the same TLRs results in release of different pattern of cytokines, depending on the patients group that is being evaluated, are discussed.